2012
DOI: 10.1111/j.1742-4658.2012.08581.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and pharmacological study of N‐linked glycosylation of the human serotonin 5‐HT7(a) receptor

Abstract: The 5-hydroxytryptamine (5-HT) 7(a) receptor is a G-protein-coupled receptor critically involved in human psychiatric and neurological disorders. In the present study, we evaluate the presence and the functional role of N-glycosylation of the human 5-HT 7 receptor. Western blot analysis of HEK293T cells transiently expressing the 5-HT 7(a) receptor in the presence of tunicamycin gave rise to a band shift, indicating the existence of an N-glycosylated form of the 5-HT 7(a) receptor. To further investigate this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Accumulation of non‐glycosylated proteins triggers the unfolded protein response (UPR), which leads to cell death primarily through apoptosis [Gellynck et al, ]. Several UPR pathways are involved in apoptosis and autophagy in response to ER stress [Hauptmann et al, ; Zhang and Kaufman, ].…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation of non‐glycosylated proteins triggers the unfolded protein response (UPR), which leads to cell death primarily through apoptosis [Gellynck et al, ]. Several UPR pathways are involved in apoptosis and autophagy in response to ER stress [Hauptmann et al, ; Zhang and Kaufman, ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, post translational modification of the 5-HT receptor is supported by several studies. Specifically, the 5-HT 7 receptor undergoes N-glycoslyation (Gellynck et al 2012 ) and C-terminal palmitoylation (Kvachina et al 2009 ). We have not tested whether a glycosylase would narrow the width of the bands observed.…”
Section: Discussionmentioning
confidence: 99%
“…Post-translational modifications of 5-HT 7 such as N-glycosylation of the N-terminus and palmitoylation of the C-terminus have been documented. N-Glycosylation does not appear to influence receptor activity, but reduced receptor expression was observed when possible glycosylation sites were mutated . Conversely, palmitoylation of the C-terminus has an impact on 5-HT 7 ’s constitutive activity .…”
Section: Constitutive Activity G-protein Interaction and Dimerizationmentioning
confidence: 93%
“…N-Glycosylation does not appear to influence receptor activity, but reduced receptor expression was observed when possible glycosylation sites were mutated. 60 Conversely, palmitoylation of the C-terminus has an impact on 5-HT 7 's constitutive activity. 61 Mutation analysis indicated that Cys 404 and 438/441 are palmitoylated via a thioester bond in an agonist-dependent manner.…”
Section: Constitutive Activity G-protein Interaction and Dimerizationmentioning
confidence: 99%